The Cochrane Database of Systematic Reviews (Complete Reviews) 2003
DOI: 10.1002/14651858.cd002982.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapeutic interventions for adults with asthma

Abstract: Background Many people have asthma, and for some their symptoms may be triggered by psychological factors. In addition compliance with medical therapy may have a psychological dimension. Therefore, psychological interventions aim to reduce the burden of symptoms and improve management of the disease. Objectives To assess the effectiveness of psychological interventions for adults with asthma. Search strategy The Cochrane Airways Group specialised register and PsycINFO were searched with pre-defined terms until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The questionnaire asked about attitudes to such innovative technology, focusing on its acceptability, practicability and impact on care (see associated with this article, located, in the online version, at Supplementary data doi: 10.1016/j.pcrj.2006.03.001). Designed by a multidisciplinary team, our questions were based on a detailed review of the literature on the use of mobile technology to monitor chronic disease [1][2][3], the process of adoption of new technologies [20], and the concepts of asthma self-management [15][16][17]. Minor adjustments were made after initial piloting.…”
Section: Questionnaire Design [21]mentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire asked about attitudes to such innovative technology, focusing on its acceptability, practicability and impact on care (see associated with this article, located, in the online version, at Supplementary data doi: 10.1016/j.pcrj.2006.03.001). Designed by a multidisciplinary team, our questions were based on a detailed review of the literature on the use of mobile technology to monitor chronic disease [1][2][3], the process of adoption of new technologies [20], and the concepts of asthma self-management [15][16][17]. Minor adjustments were made after initial piloting.…”
Section: Questionnaire Design [21]mentioning
confidence: 99%
“…Guided by written asthma action plans, some patients accept the responsibility for monitoring and adjusting their own treatment [11], whilst others fail to respond to cues for self-management [12,13] and delay important actions pending the advice of a clinician [14][15][16][17]. Novel technologies may change the dynamics of monitoring and care.…”
Section: Introductionmentioning
confidence: 99%
“…Psychotherapeutic interventions presented in the review studies included cognitive behavioral therapy, cognitive therapy, behavioral therapy, relaxation therapy, supportive counseling, hypnosis, individual and group therapy formats, and patient education programs with a psychotherapy emphasis. Fleming et al 50 found insufficient evidence to draw any definitive conclusions regarding the effectiveness of psychological interventions in asthma. The authors also reported that the inadequate number of studies (n ¼ 12) and the investigations' poor quality of study design, small sample sizes, diversity of interventions, and conflicting findings limited their systematic review.…”
Section: Asthma Treatment and Health Outcomesmentioning
confidence: 99%
“…The inadequate number of available studies for Fleming et al 50 to review reflects the lack of literature that goes beyond the mere study of educational interventions to help patients self-manage their asthma. Although numerous studies have examined asthma self-management, the majority of research has focused only on education, medication, adherence to medical regimens, and barriers.…”
Section: Asthma Treatment and Health Outcomesmentioning
confidence: 99%
“…Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] summarises the main highquality systematic reviews of psychological treatment interventions in liaison psychiatry. This updates the work of Ruddy and House 17 who reviewed both pharmacological and psychological systematic reviews of treatment interventions in liaison psychiatry from 1980 to the end of 2002.…”
mentioning
confidence: 99%